Changes in the vegetation of "Wrzosiec" mire in 1991-2009 (Western Pomerania) - Popiela, Agnieszka; Fudali, Ewa; Łysko, Andrzej (Biodiversity: Research and Conservation, 2011)
Changes in the vegetation of a mire developing in forest lake hinterland in 1991-2009 are analysed and documented three times by phytosociological method. Within peat bog "islands", situated in the southern part of the lake, the most visible change is the development of a sparse pine-stand and thick shrubs of Salix species, Frangula alnus as well as increase in the participation of Molinia caerulea and some species of Scheuzerio-Caricetea class (Calamagrostis neglecta, Carex lasiocarpa and Sphagnum fallax). Vegetation of the lag zone shows fluctuating changes in the composition of plant communities depending on the water level that periodically changes. In the north-eastern part of the lake, a consistent slow process of terrestrialization was recognised.